P235 Cerebellar ataxia in primary Sjogren's syndrome: is gluten sensitivity the answer?. (23rd April 2022) - Kon, Fu Chuen; Akil, Mohammed; Kilding, Rachael; Kuet, Kar-Ping; Shanmugarajah, Priya; Hoggard, Nigel; Hadjivassiliou, Marios
Abstract: Background/Aims: Cerebellar ataxia is an uncommon neurological complication of Primary Sjogren's Syndrome (PSS), with case reports being the highest level of evidence available. The underlying disease pathogenesis is unknown, although an immunologically mediated mechanism seems plausible. Gluten sensitivity is common amongst patients with PSS and is a known cause of immune-mediated ataxia (gluten ataxia). We aimed to investigate the presence of ataxia in patients with PSS seen in the joint rheumatology-neurology clinics at our institution, and determine if gluten sensitivity is responsible for cerebellar ataxia in some of these patients. Methods: A retrospective review of all patients who attend the rheumatology and joint rheumatology-neurology clinics was conducted. Patient data including patient demographics, the presence of gluten sensitivity-related antibodies (anti-tissue transglutaminase 2, anti-gliadin IgG and IgA, endomysial antibodies, anti-transglutaminase 6 IgG and IgA), were collected. Patients attending the rheumatology clinics with PSS were asked about the presence of any symptoms of unsteadiness. Such patients underwent MR spectroscopy of the cerebellum looking for any evidence of abnormal cerebellar metabolites (N-acetylaspartate-to-creatine (NAA/Cr) ratio <1). Electrophysiology results in the form of nerve conduction studies (NCS) or electromyography (EMG) were also collected. Results: We identified 45 patients with symptoms of impaired balance. Not all of the 236 patients with PSS who regularly attend the rheumatology clinics were assessed for any evidence of loss of balance. Nonetheless, at least 45 out of 236 patients (19.1%) complained of balance problems. The majority of these patients were female (41/45, 91.1%) with a mean age of 64.3 years. Thirty-three out of 45 patients with ataxia (73.3%) tested positive for one or more of gluten sensitivity-related antibodies, with IgA TG6 being the most common (17/33 patients, 51.5%). Out of the 33 gluten sensitive patients, 25 had MR spectroscopy of the cerebellum and 17/25 (68%) had an abnormal NAA/Cr ratio. Twenty-two patients had NCS/EMG studies performed, of which 13 (59.1%) had either a sensory-motor neuropathy or sensory ganglionopathy. Conclusion: The high prevalence of gluten sensitivity-related autoantibodies, combined with objective evidence of ataxia, suggest that gluten sensitivity may be responsible for the majority of cases of ataxia in PSS. The presence of a neuropathy in some of these patients suggests that sensory ataxia may also be contributing to the impaired balance in some of these patients. There is, however, a cohort of patients with ataxia and PSS who are not gluten sensitive. These patients may well have primary autoimmune cerebellar ataxia (PACA). Whilst a therapeutic response to a gluten free diet in patients with gluten ataxia has already been established, it remains to be seen if those patients with PSS and ataxia who have no evidence of gluten sensitivity may benefit from immunosuppression. Disclosure: F. Kon: None. M. Akil: None. R. Kilding: None. K. Kuet: None. P. Shanmugarajah: None. N. Hoggard: None. M. Hadjivassiliou: None.